CADAR DALAM PANDANGAN ORGANISASI ISLAM WAHDAH ILAMIYAH (WI) - Aisyah. M, Sitti (Mazalat: Jurnal Pemikiran Islam, 2023)
The use of the chador for Muslim women has always been an interesting topic in Islam. Scholars also have different opinions regarding the chador. There are those who regard it as an obligation, sunnah, and mubah. In fact, there are those who view that the wearing of the veil is an exaggerated attitude towards religion. The difference opinions are caused by differences in interpretation of religious texts, namely the Qur’an and hadith. One of the Islamic organisations in Indonesia that is synonymous with the chador is Wahdah Islamiyah which was founded in Makassar. They believe that wearing the chador is an obligation for Muslim women. The chador is part of the sharia that must be carried out by Muslim women. This understanding is based on the opinions of Sheikh Usaimin and Ibn Taimiyah as scholars whose opinions are often referred to by this organization. Meanwhile, for the Indonesian context, the use of the chador still has a bad stereotype. Even so, Muslim women may wear the chador, as long as it is not used as a standard of a Muslim woman's faith and piety.